2015
DOI: 10.1158/1078-0432.ccr-15-0454
|View full text |Cite|
|
Sign up to set email alerts
|

Pretreatment microRNA Expression Impacting on Epithelial-to-Mesenchymal Transition Predicts Intrinsic Radiosensitivity in Head and Neck Cancer Cell Lines and Patients

Abstract: Purpose: Predominant causes of head and neck cancer recurrence after radiotherapy are rapid repopulation, hypoxia, fraction of cancer stem cells, and intrinsic radioresistance. Currently, intrinsic radioresistance can only be assessed by ex vivo colony assays. Besides being time-consuming, colony assays do not identify causes of intrinsic resistance. We aimed to identify a biomarker for intrinsic radioresistance to be used before start of treatment and to reveal biologic processes that could be targeted to ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…However, their clinical application is still very limited due to unresolved issues such as target organ delivery and immune response circumvention (Shah and Calin, 2014). Despite these disadvantages, several studies showed their success in the downregulation of specific EMT mediators, advocating for their use as novel therapies or as sensitizers to radio-or chemotherapies able to block not only the EMT process but also metastasis (de Jong et al, 2015;Smith and Bhowmick, 2016) (Fig. 2).…”
Section: Are Anti-emt Therapies Feasible?mentioning
confidence: 99%
“…However, their clinical application is still very limited due to unresolved issues such as target organ delivery and immune response circumvention (Shah and Calin, 2014). Despite these disadvantages, several studies showed their success in the downregulation of specific EMT mediators, advocating for their use as novel therapies or as sensitizers to radio-or chemotherapies able to block not only the EMT process but also metastasis (de Jong et al, 2015;Smith and Bhowmick, 2016) (Fig. 2).…”
Section: Are Anti-emt Therapies Feasible?mentioning
confidence: 99%
“…In these cells, miR-205 downregulation determined radioresistance by targeting of PTEN [12], miR-451 increases radiosensitivity by targeting RAB14 (RAS related protein 14) [5], miR-23a is associated with modulation of radioresistance by targeting IL8 [13], and miR-185-3p regulates radioresistance, similar to miR-324-3p, by targeting WNT2B [23]. Low expression of miR-203 has been found to be correlated with local disease recurrence after radiotherapy in a series of patients with laryngeal cancer [27] whereas, in NPC, miR-203 plays important role in radiosensitivity by targeting IL8/AKT [28]. On the other hand, downregulation of miR-21 enhances radiosensitivity, but the responsible mechanism has to be clarified in NPC.…”
Section: Involvement Of Mirnas In Radioresistance Of Head and Neckmentioning
confidence: 99%
“…Meanwhile, we illustrated that miR‐1275 could increase the sensitivity of EC cells to radiotherapy both in vitro and in vivo. Intriguingly, the radiosensitization of miR‐1275 in EC was demonstrated to be attributed to the negative regulation of miR‐1275 on EC cell migration and EMT, while the association between EMT and radioresistance has already been uncovered by previous studies …”
Section: Discussionmentioning
confidence: 89%